Entry Deterrence in Hospital Procedure Markets: A Simple Model of Learning-by-Doing - Leemore Dafny (Northwestern University, Center for the Study of Industrial Organization (CSIO), 2003)
This paper examines the strategic behavior of hospitals in one of their primary output markets: inpatient surgical procedures. High levels of learning-by-doing in surgical fields may act as a barrier to entry. I investigate whether incumbent hospitals facing prospective entry in a procedure market manipulate their procedure volumes to produce such a barrier. I derive straightforward empirical tests from a model of patient demand, procedure quality, and di.erentiated product competition. Using hospital data on electrophysiological studies, an invasive cardiac procedure, I find evidence of entry-deterring investment in procedure volume. These findings suggest that competitive motivations may play a role in treatment decisions.
Keywords: 330; Krankenhaus; Wettbewerb; Markteintritt; Lernprozess; Schätzung; USA